2016
DOI: 10.1038/ja.2016.49
|View full text |Cite
|
Sign up to set email alerts
|

Quinovosamycins: new tunicamycin-type antibiotics in which the α, β-1″,11′-linked N-acetylglucosamine residue is replaced by N-acetylquinovosamine

Abstract: Tunicamycins (TUN) are potent inhibitors of polyprenyl phosphate N-acetylhexosamine 1-phosphate transferases (PPHP), including essential eukaryotic GPT enzymes and bacterial HexNAc 1-P translocases. Hence, TUN blocks the formation of eukaryotic N-glycoproteins and the assembly of bacterial call wall polysaccharides. The genetic requirement for TUN production is well-established. Using two genes unique to the TUN pathway (tunB and tunD) as probes we identified four new prospective TUN-producing strains. Chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Interestingly, the inhibition of CbMraY as determined by the FRET-based activity assay is remarkably reduced by the modification, where QVM 16:1 ( iso ) is almost 100-fold less potent compared to the corresponding tunicamycin variant Tun 16:1 ( iso ). It has previously been shown that QVM inhibits S. cerevisiae GPT as potently as tunicamycin (MIC value of 0.25 μL/ml for both compounds) in a broth dilution assay . Hence, removal of the hydroxyl group on the 6″-carbon of the tunicamycin GlcNAc has a significantly different effect on MraY inhibition as compared to GPT inhibition.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Interestingly, the inhibition of CbMraY as determined by the FRET-based activity assay is remarkably reduced by the modification, where QVM 16:1 ( iso ) is almost 100-fold less potent compared to the corresponding tunicamycin variant Tun 16:1 ( iso ). It has previously been shown that QVM inhibits S. cerevisiae GPT as potently as tunicamycin (MIC value of 0.25 μL/ml for both compounds) in a broth dilution assay . Hence, removal of the hydroxyl group on the 6″-carbon of the tunicamycin GlcNAc has a significantly different effect on MraY inhibition as compared to GPT inhibition.…”
Section: Resultssupporting
confidence: 92%
“…The uracil ring-opened analog (TunR3) was prepared by base-catalyzed hydrolysis of TunR2 . Quinovosamycins were isolated from Streptomyces niger NRRL B-3857 as described . The compounds were purified by reversed-phase HPLC on a Finnigan Surveyor instrument (ThermoFisher Scientific, West Palm Beach, FL, USA) using a specialized C 30 column typically used to purify long-chain carotenes (YMC Carotene C-30, 3 μm particle size, 4.6 × 250 mm).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations